Implementasi Zakat Pada Lembaga Amil Zakat Ibadurrahman - Mukhlis Mukhlis (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2019)
Abstract  Zakat is a system of social assistance among Muslim. The implementers of the zakat assets are directedto the mustahik people who are entitled to receive the zakat assistance. LAZ Foundation Ibadurrahman Duri took part in implementing the implementation of zakat assest to the community in Duri especially in Bengkalis District in general. Program carried out by the LAZFoundation Ibadurrahman Duri in carrying out the assets of zakat are aimed at program, Education, Health, Productive Compensation ,Consumer and Social Aid.Abstrak Zakat merupakan sebuah ibadah yang memiliki dimensi sosial di kalangan Muslim. Zakat dari para muzakki diserahkan kepada orang-orang yang berhak menerima bantuan zakat atau mustahiq. Yayasan LAZ, Ibadurrahman Duri, ikut serta dalam mengimplementasikan zakat kepada masyarakat di Duri khususnya di Kabupaten Bengkalis pada umumnya. Program yang dilakukan oleh LAZFoundation Ibadurrahman Duri dalam melaksanakan aset zakat ditujukan untuk program, Pendidikan, Kesehatan, Kompensasi Produktif, Konsumen dan Bantuan Sosial.